Implementation of Ecotheological Values in Islamic Religious Education for Flood Risk Mitigation in Sumatra and Aceh - M Mahbubi (DAAR EL-MAKRIFAH: Journal of Islamic Religious Education, 2025)
Floods that occurred in Sumatra and Aceh in 2025 indicate an increasing frequency of natural disasters affecting community life and ecosystems. One approach that can be applied to reduce disaster risk is the implementation of ecotheological values in Islamic Religious Education (IRE). This article aims to analyze how Islamic Religious Education can integrate the concept of ecotheology, which teaches responsibility toward nature and the environment as a trust from God. By focusing on teachings related to environmental protection and ecosystem sustainability within the IRE curriculum, it is expected to foster environmental awareness among younger generations. This study employs a qualitative method using a case study of flood disasters in Sumatra and Aceh as its background. The findings indicate that the application of ecotheology in IRE can enhance public understanding and concern for environmental issues, as well as encourage preventive actions in the sustainable management of natural resources. Therefore, ecotheology-based reform of the IRE curriculum can serve as an effective strategy for mitigating flood risks and other natural disasters.